Local myocardial contractility disturbances in patients with coronary heart disease and Type 2 diabetes mellitus - Z. O. Georgadze; I. G. Fomina; N. E. Gaydamakina; A. I. Frolova; T. S. Vargina; A. E. Vasilyeva; N. A. Galanina (Кардиоваскулярная терапия и профилактика, 1970)
Aim. To study local myocardial contractility (LMC) in patients with coronary heart disease (CHD) and Type 2 diabetes mellitus (DM-2). Material and methods. The study included 144 patients: 70 with CHD and DM-2 (Group I), 74 with CHD only (Group II). To study LMC disturbances, all participants underwent balanced radioventriculography (BRVG). Results. In patients with CHD and DM-2, LMC abnormalities varied from hypokinesia to akinesia and dyskinesia. In this group, comparing to participants with CHD only, the number of disturbed LMC zones was significantly greater in both left and right ventriculi. Conclusion. In CHD and DM-2 patients, who demonstrate the presence of myocardial zones hypokinetic due to chronic ischemia and diabetic cardiopathy, LMC abnormalities of both ventriculi should be timely diagnosed. LM dysfunction reversibility should be assessed in acute nitroglycerin test.